Ciclo reflexo e vulnerabilidade externa: o caso brasileiro na primeira década do século XXI - Galdeano, Juliana Aragão (2012)
This research deals with the stability in employment and its implications in labor relationships. Addresses the referred right under a modern and critical perspective, understanding the classical aspect of the stability, an overpasted legal institution unable to compatibilize with the economic and financial issues that currently permeate labor relationships. From this finding, the research seeks an alternative to compatibilize the worker's right to a work relationship that is dignified, stable, with the necessity of a productive business. For this purpose, the concept of objective good-faith is utilized. Invokes International and Foreign Rights in search of inspirational elements to the solution of the central issue. Finally, hosts the duty of motivation dismissal as the most appropriate means to the effectiveness of stability, since it can suppress the arbitrary dismissal, without preventing the occurrence of substantiated dismissals